Artemisitene Alters LPS-Induced Oxidative stress, inflammation and Ferroptosis in Liver Through Nrf2/HO-1 and NF-kB Pathway - Zhao, Changzhi; Xiao, Congshu; Feng, Songqiao; Bai, Jianxin (Frontiers in Pharmacology, 2023)
The liver plays a critical role in sepsis, which is a serious worldwide public health problem. A novel mechanism of controlled cell death called ferroptosis has recently been described. Disrupted redox equilibrium, excessive iron, and enhanced lipid peroxidation are key features of ferroptosis. It is unknown how ferroptosis affects liver damage caused by sepsis. In the present study, we aimed to elucidate the pathways and explore the impact of artemisitene (ATT) on ferroptosis in sepsis-induced liver injury. Our findings demonstrated that ATT significantly decreased liver damage and ferroptotic characteristics. Additionally, ATT significantly reduced the expression of the nuclear factor-κB (NF-κB) subunit to reduce LPS-induced hepatic oxidative stress and inflammation and upregulated the expression of nuclear factor-erythroid 2 (NF-E2)-related factor 2 (Nrf2) and its downstream protein heme oxygenase 1 (HO-1). This may offer a new strategy for preventing LPS-induced hepatic injury.